Density of localized state distribution near the valence band in stabilized a‐Se using interrupted field time of flight measurements with long interruption times. Issue 7 (19th February 2016) - Koughia, Cyril; Reznik, Alla; Allen, Christopher; Johanson, Robert; Kasap, Safa
Abstract : In the present paper, we have investigated hole transport in stabilized a‐Se films using interrupted‐field‐time‐of‐flight (IFTOF) experiments with interruption times up to 600 μs. A distinct advantage of IFTOF measurements is that one can monitor the average "free" hole concentration p ( t ) (= p ( x, t ) averaged over the thickness of the sample L ) at a given location x 1 in the sample inasmuch as the applied field is removed at a certain time t 1 for an interruption period of t i . At time t 1 + t i, the field is reapplied and the recovered photocurrent i 2 at t = t 1 + t i is measured with respect to the original photocurrent i 1 at t = t 1 . The experimental results are interpreted by the comparison of experimental photocurrent transients with numerical and Monte‐Carlo simulations of multiple trapping hole transport for different DOS models; and their agreement with a featureless DOS distribution in the vicinity of valence band is confirmed. The examination of IFTOF experiments ( i 2 / i 1 as a function of t i ) for very long interruption times puts the energy position of deep traps controlling the hole lifetime to be above 0.65 eV from E v . The results are critically discussed in view of past experiments on the DOS in a‐Se and recent structural modeling work on defects in the structure. Further, the work in this article vindicates the use of shallow trap controlled mobility and a single deep trapping time in the modeling of hole transport in recently developed a‐Se based X‐ray detectors; that is we only need shallow and deep traps to model the detector performance.